A Method for the Detection of Potential Fraud of Bringing Feline Meat in Food Chain. Issue 7 (2nd July 2016) - Amin, Md. Al; Hamid, Sharifah Bee Abd; Ali, Md. Eaqub
Abstract : Adulteration of meat in processed food is a sensitive issue since certain meat species are prohibited in some religions such as Islam and Judaism. Some meat types are also potential carrier of some deadly diseases such as severe acute respiratory syndrome, anthrax, and hepatitis. Furthermore, unconscious consumption of certain meat might lead to an allergic reaction. Feline meat is not only taboo in most cultures but also under religious prohibition. However, cat meat has been consumed in certain countries including Cambodia, South Korea, China, and Vietnam. Several polymerase chain reaction assays are proposed for the detection of feline meat. However, those assays are not tested under processed food matrices. They are also based on longer targets (672, 331, 274, 180, and 108 bp) which breakdown under compromised states. Here we documented a very short-amplicon-length (69 bp) polymerase chain reaction assay and produced strong evidence that short targets are more stable than the longer ones. Feline specificity was confirmed by cross-challenging against 17 non-target species and target stability was tested after boiling, microwaving, and autoclaving treatments under complex matrices. The tested detection limit was 0.01% (w/w) of feline meat in ternary mixtures and 0.1% (w/w) in cooked meatballs.